Epidemiological study of respiratory disease in workers exposed to polyvinylchloride dust. Issue 9 (September 1980) - Soutar, C A; Copland, L H; Thornley, P E; Hurley, J F; Ottery, J; Adams, W G; Bennett, B
Abstract : The respiratory health of workers exposed to polyvinylchloride (PVC) dust has been investigated in 818 men sampled from the work force of a factory manufacturing PVC. In a cross-sectional survey, the lung function and prevalences of respiratory symptoms and chest radiographic abnormalities were compared with estimates of individual PVC dust exposures based on detailed occupational histories and current measurements of respirable PVC dust. Complaints of slight exertional dyspnoea were associated with PVC dust exposure, though age and smoking effects were much stronger. The forced expired volume in one second (FEV1) and forced vital capacity (FVC) were inversely related to dust exposure after age, height, and smoking effects had been taken into account. This effect was seen principally in cigarette smokers, and there was suggestive evidence that PVC dust exposure and cigarette smoking interacted in the reduction of FEV1 and FVC. Gas transfer factor was not related to dust exposure. The chest radiographs were read according to the ILO U/C classification by three experienced readers. One reader recorded a low prevalence of small rounded opacities, and these were not related to age or dust exposure. Another reader recorded a higher prevalence of small rounded opacities category 0/1 or more, and these were related to age but not to dust exposure. The third reader recorded the highest prevalence of small rounded opacities (though none greater than category 1/1), and these were independently related both to age and to PVC dust exposure, indicating an effect of PVC dust on the appearance of the chest radiography. These appearances were so slight that only the higher sensitivity of this reader in the interpretation of profusion of small rounded opacities on the ILO U/C scale enabled detection of this effect of PVC dust. In conclusion, exposure to PVC dust is associated with some deterioration of lung function, slight abnormalities of the chest radiograph, and complaints of slight dyspnoea. The mean decline in FEV1 associated with the average dust exposure experienced in the study was small, though some of the men with higher dust exposures may have suffered clinically important loss of lung function as a result of their occupation.